Tuktu Past, Present, and Future: State of Torngat Mountains Caribou and their Forage in a Changing Environment - Johnson, Alexandra (University of Waterloo, 2022)
Caribou (Rangifer tarandus) populations are in decline across Canada, making this charismatic species a major conservation concern. For Inuit of Northern Labrador and Quebec, caribou are a cultural keystone species with nutritional, cultural, and spiritual value. Inuit have long been aware that the Torngat Mountains Caribou (TMC) population is distinct from the overlapping George River Caribou (GRC) herd, but this distinction has only recently been recognized by federal and provincial governments. Therefore, limited TMC specific data are available. The objective of this thesis is to summarize existing information on the TMC, identify knowledge gaps, and contribute to the growing body of research on the TMC. One threat facing the TMC is climate change. Arctic warming has resulted in shrub expansion in Eastern Canada’s tundra which, in turn, has negatively impacted lichens, an important caribou food source. This study investigates changes to caribou forage availability due to ambient and experimental warming at two tundra sites located within the range of the TMC in Nunatsiavut, Labrador. The main questions we address are: 1) What proportion of total vegetation is suitable caribou forage and how has this changed with time and experimental warming? 2) Which forage species are most impacted by recent climate change? To answer these questions, we analyzed vegetation data collected over a 14-year period within the TMC’s range. Permanent, control and warming plots were established at Nakvak Brook and Torr Bay in 2007 and 2009 respectively and re-sampled every 3-6 years. From these vegetation data, we identified species of high, medium, and low caribou forage quality based on published literature. We then modelled the observed changes in forage availability. Results of this study found that caribou are more likely to be forage limited in the winter than during the summer. Consistent with shrub expansion, we found that birch, and ericaceous shrub species increased with time at Torr Bay. Conversely, we found that willow ...